2005
DOI: 10.1161/01.res.0000165478.06813.58
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Overexpression of O -GlcNAcase Improves Contractile Function in the Diabetic Heart

Abstract: Abstract-To examine whether excessive protein O-GlcNAcylation plays a role in the dysfunction of the diabetic heart, we delivered adenovirus expressing O-GlcNAcase (Adv-GCA) into the myocardium of STZ-induced diabetic mice. Our results indicated that excessive cellular O-GlcNAcylation exists in the diabetic heart, and that in vivo GCA overexpression reduces overall cellular O-GlcNAcylation. Myocytes isolated from diabetic hearts receiving Adv-GCA exhibited improved calcium transients with a significantly short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
187
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(197 citation statements)
references
References 59 publications
7
187
3
Order By: Relevance
“…Several groups have shown that prolonged elevation of O-GlcNAc levels attenuates insulin signaling [17,22], though this issue is far from reconciled [42]. Hu et al showed that altered O-GlcNAcylation in diabetic hearts contributes to cardiac dysfunction and calcium handling [43]. Such efforts support the emerging notion that O-GlcNAc signaling participates in the pathogenesis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that prolonged elevation of O-GlcNAc levels attenuates insulin signaling [17,22], though this issue is far from reconciled [42]. Hu et al showed that altered O-GlcNAcylation in diabetic hearts contributes to cardiac dysfunction and calcium handling [43]. Such efforts support the emerging notion that O-GlcNAc signaling participates in the pathogenesis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were made hyperglycaemic by a single injection of freshly prepared STZ solution (200 mg/kg body weight in citrate saline, pH 4.2, i.p. ; Alexis, Lausanne, Switzerland) [26]. The mice were housed in cages of four mice each and had unlimited access to water and standard mouse chow.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, elevating levels of glucose in neonatal cardiomyocytes resulted in augmented O-GlcNAc levels and subsequently reduced function of mitochondrial electron transport complexes I, III, and IV (Hu et al 2005), however, its role in stress has not been studied yet. Interestingly, overexpressing O-GlcNAcase to reduce O-GlcNAc levels can reverse the effects of reduced mitochondrial function when glucose levels are elevated (Hu et al 2005). …”
Section: Mitochondrial Dynamicsmentioning
confidence: 99%